Bioética e biodireito: interfaces e confluências - Lima, Walber Cunha (2012)
This thesis addresses the development of technoscience in times of transnational globalization and highlights the vulnerability of the discourse of social progress, which may be replaced by evidence of social risk before the artificiality of nature and humanity. That demands an ethical and legal responses to events that impose the necessity of an ethical control in biotechnology research involving human beings contributing to the rise of Bioethics and Biolaw as fields of knowledge. This theme is studied from a multidisciplinary perspective seeking a dynamic dimension in the interpretation of research data reconnecting Social Sciences to Legal Sciences (Biolaw) and to Philosophy (Bioethics), in order to obtain answers to the problems posed. The objective delimited is to examine the interfaces between Biolaw and Bioethics, in order to observe the confluence of these areas of knowledge. Biolaw is considered as a new legal branch derived from the paradigmatic transition of Law and wonders how it will stand before questions resulting of social transformations caused by biotechnological development that endangers humans and society. It is concluded that the relationship between Bioethics and Biolaw is recursive and inseparable and it contributed to the "unthink" of traditional legal model of linear view/reductionist allowing that the "certainties" will be replaced by "possibilities", which comes to enable Biolaw to confront the issues caused by the development of biotechnology that violates physically and morally the human person. It is perceived, therefore, that Biolaw is driven and aided by bioethical reflections and it positions itself before the dilemmas caused by biotechnology in creating, interpreting and applying coercive rules which aims to protect the human being, his offspring and society